SELECTED ISSUES OF HEALTH EDUCATION IN THE IMPLEMENTATION OF RUNNING DURING A PANDEMIC - Skalski, D. W.; Kowalski, Damian; Nesterchyk, Natalia; Kindzer, Bogdan; Korol, Olena (Rehabilitation and Recreation, 2022)
Sport supports the immune system, thanks to which a person becomes stronger in the fight against viruses, although whether also with the coronavirus, it is difficult to say at this stage of its understanding. Keep in mind that sports are mostly physical exertion that may involve some risk. Therefore, before taking it, the body should be checked, especially in terms of cardiology. Sport is good for health, but a comprehensive diagnosis of your health with a specialist will not hurt. In the current situation, it is difficult, so in the presence of chronic diseases, it is worth consulting a doctor or physiotherapist using teleportation. When the undertaken physical activity does not differ from the usual one or its intensity is lower, the risk seems to be minimal. The first and most important rule is that training should be carried out individually! Avoiding contact with other people will definitely increase your chances of staying healthy. However, from the methodical point of view, the training should last at least 20 minutes to be effective. For training, you do not waste time on changing clothes, bathing and all this logistics. In order to feel the lasting effects of training work, it should be performed at least 3 times a week. If the interval between workouts is more than 2 days, the body forgets the previous activity and there is no building process. And nothing by force. Sport is supposed to be fun and help you survive this difficult time in a slightly better psychophysical condition. While the pandemic is still present in our lives, running outside is not prohibited. For outdoor training, you can go to the city park, the garden in Jordan, the promenade, boulevards or the nearby forest. This is good news, because anyone who has been running for some time knows that a treadmill is not able to replace outdoor activity. However, when going to training, one must not forget that the epidemic is still going on and that it is necessary to constantly take precautions. Fighting the epidemic involves limiting social contacts. The lockdown forced the closure of schools, educational establishments, other institutions and public benefit organizations. From the moment of the pandemic, the classes were conducted online for the majority of students. Distance learning has become a compulsory safeguard against the COVID-19 threat. Adults were forced to stay at home, possibly switching to remote work. However, the need to protect communities from the coronavirus shows increased, long-term and adverse health consequences, caused by stress, anxiety, anxiety and a sense of helplessness during an epidemiological crisis.